An Ultrasound‐Responsive Theranostic Cyclodextrin‐Loaded Nanoparticle for Multimodal Imaging and Therapy for Atherosclerosis (Small 31/2022). Issue 31 (4th August 2022) - Mehta, Sourabh; Bongcaron, Viktoria; Nguyen, Tien K; Jirwanka, Yugandhara; Maluenda, Ana; Walsh, Aidan P G; Palasubramaniam, Jathushan; Hulett, Mark D; Srivastava, Rohit; Bobik, Alex; Wang, Xiaowei; Peter, Karlheinz
Abstract : Atherosclerosis Imaging and Therapy In article number 2200967, Xiaowei Wang, Karlheinz Peter, and co‐workers show that theranostic nanoparticles made of air can deliver a near‐infrared fluorescence dye, cyclodextrin, to be used as a contrast agent for ultrasound and fluorescence imaging and as ultrasound‐responsive anti‐atherosclerotic drug, achieving reduction of cholesterol in plaques after ingestion of nanoparticle by monocytes/macrophages.